ASPEK YURIDIS NORMATIF TENTANG PILOT PESAWAT UDARA - Nrangwesti, Ayu (Syiar Hukum, 2011)
The pilot of the aircraft had the role that was very important in the flight, especially to guarantee the security and the safety of the flight. Therefore, the pilot must know about his authority as the pilot. The authority of this pilot related to the competence certificate and the licence. Giving of the competence certificate and the licence  to the pilot of the aircraft must meet certain conditions and was given by certain sides. Legally, the competence certificate and this licence were arranged in several instruments of the national air law and the Internasional  air Law. The instrument of this law in part of regulations number 1 in 2009 about the Flight, Chicago  convention1944 about  the Internasional Civil Aviation, Annex 1 of the Personnel Licensing and Part 20 Civil Aviation Safety Regulation. The role of the pilot as the aircraft guide(the pilot technically) have  relation to the role of the pilot  as the yuridically manner ( the commander of the aircraft). juridically the role of the pilot  related to his authority to take part in playing to  combatting crimes that were carried out in the aircraft that was flying. The authority of the pilot as the commander of the aircraft in arranged in the Tokyo Convention 1963.